THE EMINENT MARTYR’S SANCTIFICATION - Процюк, С. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article discloses some aspects of Mykola Bazhan’s creative work. It concerns the poet’s heavy psychological split personality within the severe censorial frames of the totalitarian regime. The attempt is also made to explore the poet’s complicated and controversial inner struggle that reflected itself on the contents of Mykola Bazhan’s books.